A DFT study on the crystal stability, mechanical, electronic and thermodynamic properties of Ir3Nb under high pressure and temperature. (February 2022) - Wang, Baowen; Xiong, Kai; Sun, Zepeng; Li, Wei; Jin, Chengchen; Zhang, Shunmeng; Guo, Lei; Mao, Yong
Abstract: The crystal stability, mechanical, electronic and thermodynamic properties of Ir3 Nb at high pressures and high temperatures were systematically investigated by first-principles calculations based on density functional theory. The obtained lattice parameters are consistent with available experimental and theoretical results. The Ir3 Nb crystal maintains its crystal stability in the range of 0–100 GPa and 0–1600 K. With the increase of pressure, the lattice parameter decreases, while the elastic constants and mechanical moduli ( B, G, E ) increase. The study shows that Ir3 Nb exhibits intrinsic brittleness and mechanical anisotropy. There is no ductile-brittle transition occurred in the pressure range of 0–100 GPa according to the Pugh's ratio and Poisson's ratio analyses. The mechanical anisotropy of Ir3 Nb is significantly enhanced with the increase of pressure. The electronic analyses show that the Ir-5 d and Nb-4 d electrons hybrid to form a pseudogap on the electronic density of states curves. The pseudogap is gradually widened with the increase of pressure, which means a stronger Ir-Nb bonding strength under high pressure. The study also shows that the elastic constants and mechanical moduli decrease with elevated temperature. Thermodynamic analysis indicates that the thermal expansion coefficient and heat capacity increase as temperature increases, especially at low temperatures. The sound velocity and Debye temperature increase with the increase of pressure. Highlights: Mechanical, electronic and thermodynamic properties of Ir3 Nb were systematically studied at high pressure and temperature. The phonon spectra and AIMD simulations were used together to prove the dynamical stability of Ir3 Nb. Directional bonds were identified to form between Ir and Nb atoms, which is contributed by the Ir-5 d and Nb-4 d electrons.